NURSE WORK STRESS DURING THE COVID-19 PANDEMIC - Annisa Rahmi Galleryzki; Rr. Tutik Sri Hariyati; Kuntarti Kuntarti (2022)
Nurse Work Stress During The COVID-19 Pandemic. COVID-19 does not only cause problems in physical conditions but also has the potential to cause problems in mental health, including for nurses who are at the forefront of handling COVID-19. This study aims to see a description of the work stress felt by nurses during the COVID-19 pandemic at a COVID-19 referral hospital. The sample consisted of 133 nurses. The results of the analysis show that the average work stress of nurses is 106.19 (32.2%). The highest perceived work stress was inadequate preparation 7.31 (47.8%), while the lowest perceived work stress was a conflict with nurses 10.02 (22.33%). The description of nurses' work stress in this study was lower than in previous studies. This can be because nurses are able to realize the pandemic conditions, work carefully and make better preparations. Management support is very much needed in making the right rules, especially in preventing and controlling the transmission of the Covid-19 virus.